Molecular targets of neuroplasticity in ischemic stroke: insights from GEO database, single-cell analysis and immune infiltration analysis - Haoyue Yang; Haoyue Yang; Zekun Li; Lu Zhang; Lu Zhang; Haifeng Zhang; Haifeng Zhang; Yang Liu; Yang Liu; Wei Chen; Wei Chen; Feng Zhang (Frontiers in Aging Neuroscience, 2025)
This study is aimed to identify diagnostic and therapeutic biomarkers related to neuroplasticity in IS. Gene expression profiling (GSE61616) was derived from GEO, and neuroplasticity-related genes were obtained from the GeneCards databases. The overlapping genes related to neuroplasticity were processed for GO and KEGG analysis. The protein interaction network and hub genes were identified using Cytoscape and the PPI network. Then we predicted the potential TFs and miRNAs related to hub genes. Single-cell analysis was performed to explore cellular localization and intercellular communications related to hub genes in GSE167593. Immune infiltration characteristics were explored via GSVA package. The correlation between various immune cells and hub genes (CCR5 and CXCR4) was calculated via linKET package. Finally, DGIdb database was used for screening small-molecule drugs of CCR5 and CXCR4. Our study screened five significant neuroplasticity-related hub genes (CCR5, CXCR4, TIMP1, GRIN1, and GRM1). Moreover, single-cell analysis revealed that the CCR5 was specifically expressed in microglia and macrophages, while the CXCR4 was specifically expressed in T cells, NK cells, macrophages, and granulocytes. Immune infiltration and correlation analysis revealed a positive association of CCR5 with aDCs and T helper cells, while CXCR4 was positively correlated with CD8+ T cells, but negatively correlated with Tfh. Finally, the Leronlimab, Ulocuplumab, Burixafor, and MSX-122 are promising drugs to treat IS via targeting on CCR5 and CXCR4. In conclusion, our findings suggest that CCR5 and CXCR4 are promising targets for enhancing neuroplasticity post-ischemic stroke, thus providing potentially effective and reliable therapeutic targets for future interventional strategy.